Study of the Statistical Characteristics of Artificial Source Signals Based on the CSES - Huang, Jianping; Jia, Juan; Yin, Huichao; Li, Zhong; Li, Jinwen; Shen, Xuhui; Zhima, Zeren (Frontiers in Earth Science, 2022)
The ground-based artificial source electromagnetic signal transmitted to space will form a pair of high intensity regions over the station and its conjugate points. In order to study the position and intensity of the strongest points in the two regions, the power spectrum density of electric field onboard Zhangheng-1 satellite (CSES) was selected when it passed over NWC artificial source transmitting station. The selected frequency is centered at 19.8KHz with the bandwidth of 200Hz.The strongest point is defined as the location with the maximum power spectrum density in ±10° around NWC station and in 5 days which are the revisiting period of CSES. The results show that statistic characteristics of strongest points vary as day/night, local/conjugate point, longitude/latitude, different components of electric vectors. In terms of longitude deviation, it is mostly westward offset in the night and both sides in the day over the NWC, but over the conjugate point is on the contrary. In terms of latitude deviations, it is equator-ward in the night and the same in the day with smaller deviation. While over the conjugate point, it is northward offset in the day and both in the night with bigger offset. In terms of intensity, it is stable without obvious seasonal changes over NWC and its conjugate point. The intensity of PSD is higher in the night than that in the day. For the PSD intensity of the 3 components, the descending order over NWC is Ead, Eab, Ecd in the night and Ecd, Ead, Eab in the day and over the conjugate point is on the contrary.